2017
DOI: 10.3389/fpls.2017.01945
|View full text |Cite
|
Sign up to set email alerts
|

Inspecting the True Identity of Herbal Materials from Cynanchum Using ITS2 Barcode

Abstract: Cynanchum is a large genus with some important medicinal species in China. The medicinal species in Cynanchum are easily confused, leading to potential safety risks. In this study, the internal transcribed spacer 2 (ITS2) barcode was used to discriminate the medicinal plants in Cynanchum. The identifying capability of ITS2 was assessed using the specific genetic divergence, BLAST1, neighbor-joining (NJ) tree, maximum-likelihood (ML) tree, and single-nucleotide polymorphism (SNP) methods. Results indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 57 publications
2
12
0
Order By: Relevance
“…Recently, DNA barcoding technique has been widely used for species discrimination. Up to now, matK , rbcL , psbA - trnH , internal transcribed spacer (ITS), and ITS2 are the most commonly used regions for DNA barcoding in plants [31,32,33,34]. In this study, we systematically evaluated the feasibility and identification efficiency of four generally acknowledged single loci, namely, rbcL , psbA - trnH , ITS, and ITS2, and their combinations to discriminate the Epimedium species distributed in China to identify the most suitable barcodes for genus Epimedium and provide effective information for the species identification of this genus.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, DNA barcoding technique has been widely used for species discrimination. Up to now, matK , rbcL , psbA - trnH , internal transcribed spacer (ITS), and ITS2 are the most commonly used regions for DNA barcoding in plants [31,32,33,34]. In this study, we systematically evaluated the feasibility and identification efficiency of four generally acknowledged single loci, namely, rbcL , psbA - trnH , ITS, and ITS2, and their combinations to discriminate the Epimedium species distributed in China to identify the most suitable barcodes for genus Epimedium and provide effective information for the species identification of this genus.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Li et al (2014) identified the herbal medicinal materials from Aristolochia using the matK, rbcL, psbA-trnH, and trnL-trnF DNA regions. Guo et al (2017) identified the herbal materials from Cynanchum using the ITS2 barcode; Gong et al (2018) constructed a DNA barcode reference library for "Nan Yao" (crude drugs mainly produced in or imported through tropical and subtropical China, especially the Lingnan region, i.e., the territories south of the Nanling Mountains) using ITS2; and Jiao et al (2018) identified the medicinal Polygonati Rhizoma (a traditional medicinal and edible product with Polygonatum polysaccharides, saponins, phenols, and flavonoids) efficiently and accurately using ITS2 and psbA-trnH sequences. This shows that the selection of molecular markers for plant groups in China still relies heavily on the combination of multiple markers.…”
Section: Standard Dna Barcodes For Plant Groups Need Further Explorationmentioning
confidence: 99%
“…The medicinal species in Cynanchum are easily confused, leading to potential safety risks. Through the development of identification technology, researchers identified Cynanchi Atrati Radix et Rhizoma ( Baiwei in Chinese) showed a potential safety problem by discriminating 64 commercial samples of the medicinal plants [ 116 ]. By employing the internal transcribed spacer 2 (ITS2) barcode, researchers surveyed the authentication and greatly improved the identification efficiency and accuracy of commercial herbal medicines in the Cynanchum genus [ 13 , 114 , 116 ].…”
Section: Safety and Quality Control Of Cynanchum Paniculmentioning
confidence: 99%
“…Through the development of identification technology, researchers identified Cynanchi Atrati Radix et Rhizoma ( Baiwei in Chinese) showed a potential safety problem by discriminating 64 commercial samples of the medicinal plants [ 116 ]. By employing the internal transcribed spacer 2 (ITS2) barcode, researchers surveyed the authentication and greatly improved the identification efficiency and accuracy of commercial herbal medicines in the Cynanchum genus [ 13 , 114 , 116 ]. In 2006, Deng et al reported quick and easy identification of paeonol content by the microwave-assisted extraction and headspace single-drop microextraction (MAE-HS-SDME) method for quality monitoring for the two herbal medications of Cynanchum paniculatum and Paeonia suffruticosa [ 13 , 114 , 117 ].…”
Section: Safety and Quality Control Of Cynanchum Paniculmentioning
confidence: 99%